REPLACING OF SOYA BEANS BY DUCK WEED (LEMNA GIBBA) IN THE DIETS OF FRY OF COMMON CARP (CYPRINUS CARPIO) - saleh, J. H. (Iraqi Journal of Aquaculture, 2022)
Soya bean was replaced in ratio of 20% and 40% by a dry duck weed in the diet of common carp fry under laboratory conditions. The results showed that the fry which fed on duck weeds gives a final total length of 40.15mm, final wet weight of 1.105 gm and final increase of weight was 0.966gm. The group of larvae which fed on soya bean recorded 37.230 mm, 0.750 gm and 0.618 gm respectively.